MAIN STAGES OF RUSSIAN INFLATION: THEIR CHARACTERISTICS AND FEATURES - I. N. Primyshev (Вестник университета)
The relevance of scientific research on the nature and specifics of inflationary processes in domestic economic thought, starting in the 1990s of the twentieth century, is associated with the peculiarities and difficulties of the development of the Russian economy in the transition from a command-and-control economy to a market economy. In this study, the author analyses inflation over a thirty-year period from the early 1990s of the twentieth century to the present. The paper describes in detail each stage of development of inflationary processes. The article analyses monetary policy at each stage of inflation development. The author determines the  features of Russian inflation over the ten-year period 2008-2018. The study considers the main anti-inflationary  measures applied at each stage. The article characterizes the development and features of inflation at the present stage (2019-2020). The paper concludes that the Russian Federation is dominated by the cost inflation factor, which must be taken into account when forming anti-inflationary measures.